Cost-effectiveness of colorectal cancer screening and treatment methods: Mapping of systematic reviews - Hossein Mashhadi Abdolahi; Ali Sarabi Asiabar; Saber Azami-Aghdash; Fatemeh Pournaghi-Azar; Aziz Rezapour (Elsevier, 2018)
Objective: Due to extensive literature on colorectal cancer and their heterogeneous results, this study aimed to summarize the systematic reviews which review the cost-effectiveness studies on different aspects of colorectal cancer. Methods: The required data were collected by searching the following key words according to MeSH: "colorectal cancer," "colorectal oncology," "colorectal carcinoma," "colorectal neoplasm," "colorectal tumors," "cost-effectiveness," "systematic review," and "meta-analysis." The following databases were searched: PubMed, Cochrane, Google Scholar, and Scopus. Two reviewers evaluated the articles according to the checklist of "assessment of multiple systematic reviews" (AMSTAR) tool. Results: Finally, eight systematic reviews were included in the study. The Drummond checklist was mostly used for assessing the quality of the articles. The main perspective was related to the payer and the least was relevant to the social. The majority of the cases referred to sensitivity analysis (in 76% of the cases) and the lowest point also was allocated to discounting (in 37% of cases). The Markov model was used most widely in the studies. Treatment methods examined in the studies were not cost-effective in comparison with the studied units. Among the screening methods, computerized tomographic colonography and fecal DNA were cost-effective. The average score of the articles' qualities was high (9.8 out of 11). Conclusions: The community perspective should be taken into consideration at large in the studies. It is necessary to pay more attention to discounting subject in studies. More frequent application of the Markov model is recommended.